Asuhan Keperawatan Lansia Hipertensi dengan Insomnia Melalui Relaksasi Otot Progresif di RSUD Embung Fatimah Batam - Irma Mahlisa; Nelli Roza (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Hypertension is one of the most common chronic diseases among the elderly and is often accompanied by insomnia. This condition can increase anxiety and reduce quality of life. Progressive Muscle Relaxation (PMR) is an effective non-pharmacological therapy to lower blood pressure and improve sleep quality. This paper describes nursing care for elderly patients with hypertension and insomnia through PMR application at RSUD Embung Fatimah Batam City in 2025. A case study approach was used through the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The main nursing diagnosis was sleep pattern disturbance related to physical discomfort and anxiety. Interventions included education and PMR exercises for six consecutive days. Results showed blood pressure decreased from 180/100 mmHg to 130/80 mmHg, sleep quality improved from difficulty sleeping to 6–7 hours per night, and anxiety levels reduced. Progressive muscle relaxation therapy proved effective as an independent nursing intervention to reduce blood pressure and improve sleep quality in elderly patients with hypertension and insomnia. Nurses should use this therapy as a routine non-pharmacological intervention in gerontological nursing practice.